Energy Aware Offloading in Cloud Assisted Mobile Environment - Arya, Nancy; Choudhary, Sunita; Taruna, S (International Journal of Computer Sciences and Engineering, 2019)
In the last one decade, the utilization of mobile technology has increased tremendously. The development in the mobile technology is leading to the innovations in the smart phones. Now, smart phones are not only used for communication but also capable to support number of complex applications, mostly requires high computational power. Although these smart phones have several resource issues related to power capacity, data transfer, storage capacity, security and limited processing power etc. Power capacity is one of the most crucial issue of the current smart phones. However, mostly mobile devices emphasize on many power management functions to save the power but the overall saving is much less than actual requirement. In this situation, Mobile Cloud Computing provides good option of task offloading where any intensive computations are migrated to the remote servers or cloud. Mobile Cloud Computing is a new network paradigm which merged the features of mobile computing and cloud computing to overcome the issues of mobile devices. It can also be a power saving paradigm which needs serious attention. Thus, this paper proposed a novel approach for energy aware task offloading for mobile cloud environment.